Lei 10.639/03 e Lei 11.645/08 : possibilidades e desafios para a construção de uma educação antirracista : Escola Estadual São Pedro Apóstolo - Pedra Preta-MT - Cunha, Maria de Fatima Limeira da Silva (2021)
Aiming to investigate the possibilities and challenges for the construction of an anti-racist education in Escola Estadual São Pedro Apóstolo in Pedra Preta-MT, considering the implementation of Laws 10.639/03 and 11.645/08. We emphasize that the data collecting procedure took place initially through a bibliographic survey, followed by the documentary research - Pedagogical Political Project and, then, by sending online questionnaires to the research participants. The research was developed at the São Pedro Apóstolo State School in the city of Pedra Preta-MT, seeking for a significant sample for this purpose, we worked with fourteen (14) participants, twelve (12) students registered in classes from the 6th to the 9th grade, one (01) History teacher and one (01) school principal. For data collecting, the survey participants answered an online questionnaire, available to them through Google Forms. It was necessary to collect data in this way due to the Covid-19 pandemic, which imposed a strict social isolation on us. Data collecting would be in person, however, the pandemic forced us to modify the methodology initially proposed, considering that we need to protect ourselves and also think about the health of the students, teacher and school director involved in this research. The time frame of the study considered the period from 2003 to 2020, with emphasis on all legislation aimed at the ethnic-racial issues approved in that period of time, until the time of this research. The theoretical perspective adopted to develop this research is the Decolonial Perspective, developed by thinkers such as the Argentine philosopher Enrique Dussel, the Peruvian sociologist Aníbal Quijano, the Argentine-North American semiologist and cultural theorist Walter Mignolo, the Puerto Rican sociologist Ramón Grosfoguel, the American linguist based in Ecuador Catherine Walsh, the Puerto Rican philosopher Nelson Maldonado Torres, the Colombian anthropologist Arturo Escobar. In addition to these scholars, the ideas and concepts developed by Nilma Lino Gomes, Abdias Nascimento Bell Hooks, Kabengele Munanga, Djamila Ribeiro, Lilia Moritz Schwarcz, and other researchers who helped us to understand the issue of racism, ethno-racial relations and the importance of a liberating, emancipatory and engaged education in the fight against racism and racial discrimination. The research method was based on the qualitative approach, which technique used is content analysis, developed by Laurence Bardin (2011). Observation was used as a complementary resource to deepen issues related to the development of educational practices aimed at combating racism, prejudice against racial discrimination in the school environment.